Serum testosterone does not affect bone mineral density in postmenopausal women - Arpaci,Dilek (2015)
Objective The purpose of the present study was to investigate the correlation between serum testosterone levels and bone mineral density (BMD) in postmenopausal women.Materials and methods The study group was made up of postmenopausal women admitted to our tertiary center. Serum calcium, phosphorus, albumin, parathyroid hormone (PTH), thyrotropin (TSH), 25-OH vitamin D, and total testosterone concentrations were measured. Subjects were categorized into three groups regarding bone mineral density (BMD) values: normal (n = 22), osteopenia (n = 21), and osteoporosis (n = 21). Subjects were also categorized into three groups according to serum testosterone levels: low testosterone (n = 10), normal testosterone (n = 42), and high testosterone (n = 12).Results No significant difference was found for serum testosterone, TSH, calcium, phosphorus, albumin, PTH, and 25-hydroxyvitamin D levels among patients with normal BMD, osteopenia, and osteoporosis (p > 0.05). Lumbar spine, total femur, femoral neck, trochanteric, intertrochanteric, and Ward’s triangle BMD values were similar for the different testosterone levels (p > 0.05).Conclusion There was no correlation between serum testosterone levels and patient age, body-mass index, or any measured BMD values. Given the findings in our study, which failed to demonstrate a statistically significant relationship between testosterone and BMD, adjustment of other risk factors for osteoporosis might have a more distinctive effect in this setting.